LITERATURE REVIEW: DIGITAL COMIC IMPLEMENTATION IN CHEMISTRY LEARNING IN HIGH SCHOOL - Silalahi, Yoisi Fortuna; Saputri, Mitha; Wijaya, Putri Regita; Marida, Lala (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Chemistry learning material is difficult and abstract material. Learning media is an alternative used by teachers as a tool to channel content or teaching messages so as to attract students' attention. One of the chemistry learning media used is digital comics. This literature review aims to examine the implementation of digital comic-based learning media in chemistry learning in high schools. The method used in this literature review is SLR (Systematic Literature Review). Data collection uses Google Scholar with a time span from 2013-2023. The articles used in this literature review were 34 national journal articles and 17 international journal articles. Based on the results of this literature review, it shows that the application of using digital comic media such as comic life, fb reader, melsyaapps, and line webtoon in chemistry learning can convey information easily to students so that it can improve student learning outcomes, creative thinking skills, and develop student character values such as caring for the surrounding environment, being good at interacting with individuals and groups, and having a high curiosity. Keywords: digital media, digital comics, chemistry learning